Turning over a New Leaf Change and Development in the Medieval Book - Kwakkel, Erik (Leiden University Press, 2012)
Books before print - manuscripts - were modified continuously throughout the medieval period. Focusing on the ninth and twelfth centuries, this volume explores such material changes as well as the varying circumstances under which handwritten books were produced, used and collected. An important theme is the relationship between the physical book and its users. Can we reflect on reading practices through an examination of the layout of a text? To what extent can we use the contents of libraries to understand the culture of the book? The volume explores such issues by focusing on a broad palette of texts and through a detailed analysis of manuscripts from all corners of Europe.